(untitled) (Journal of Hama University, 2024)
The study aimed to determine the role of banking information systems with its components (inputs، operations، outputs) in improving credit risk management during the reconstruction phase in commercial banks in Lattakia Governorate. The researcher relied on the deductive approach، and relied on the descriptive approach to describe the research variables and analyze them based on the primary data collected، where the researcher conducted a field study on the branches of Syrian commercial banks in Latakia Governorate to collect the necessary primary data، and the variables were measured on all the primary data that were completed. It was collected through two questionnaires designed through the researcher’s review of previous studies and literature (a questionnaire for banking information systems and credit risk management، distributed to workers in the upper and middle management levels)، and in order to test the hypotheses، the researcher unloaded the primary data into a database that was analyzed using the SPSS program. Version /20/. The study reached a number of results، including: There is a weak correlation between the banking information system and the improvement of credit risk management، where the correlation coefficient reached 0.476، and the coefficient of determination was 0.226، which indicates that 22.6% of the changes in credit risk management follow changes in banking information systems، which means that there is a relationship between the banking information system and credit risk management.